PENGARUH LITERASI POLITIK DAN PENGGUNAAN MEDIA SOSIAL TERHADAP PARTISIPASI POLITIK MASYARAKAT DI KOTA MEDAN - Marchel Given Siagian (SUAN PUBLISHER, 2026)
Democratic maturity within modern urban governance requires civic political participation that is not merely grounded in quantitative electoral mobilization, but anchored in rational considerations and substantive comprehension of state dynamics. In the contemporary digital democracy era, Medan City confronts a distinctive challenge marked by a disparity between the high penetration of social media as a public information conduit and variations in civic political literacy levels. This study aims to analyze and quantify the empirical effect of political literacy and social media usage on the political participation of citizens in Medan City, both partially and simultaneously. Employing an explanatory correlational quantitative approach, this research surveyed 150 eligible voters aged years in Medan City who actively use social media, selected via purposive sampling. Primary data were gathered through a structured 5-point Likert scale questionnaire tested for validity and reliability, and analyzed using multiple linear regression in IBM SPSS Statistics version 26. The empirical findings reveal that political literacy exerts a positive and significant effect on political participation (; ), and social media usage similarly demonstrates a positive and significant effect on political participation (; ). Simultaneously, both independent variables significantly influence civic political participation (; ) with a coefficient of determination () of 0.517. This confirms that 51.7% of the variance in political participation across Medan City is collectively explained by political literacy and social media usage, while the remaining 48.3% is governed by external factors. These findings highlight the strategic urgency of digital civic education to transform online media engagement into critical, well-informed, and constructive democratic participation.